DNA binding properties, histidine interaction and cytotoxicity studies of water soluble ruthenium(ii) terpyridine complexes. Issue 11 (8th February 2016) - Lazić, Dejan; Arsenijević, Aleksandar; Puchta, Ralph; Bugarčić, Živadin D.; Rilak, Ana
Abstract : UV-Vis spectroscopy studies, viscosity measurements and competitive binding studies with EB have revealed the ability of the complexes to bind to CT DNA covalently through N7 of guanine residues and non-covalently through intercalation. Abstract : In this study, two representatives of previously synthesized ruthenium(ii ) terpyridine complexes, i.e., [Ru(Cl-tpy)(en)Cl][Cl] (1 ) and [Ru(Cl-tpy)(dach)Cl][Cl] (2 ), were chosen and a detailed study of the kinetic parameters of their reactivity towardl -histidine (l -His), using the UV-Vis and 1 H NMR techniques, was developed. The inner molecular rearrangement from N3-coordinatedl -His to the N1 bound isomer, observable in the NMR data, was corroborated by DFT calculations favoring N1 coordination by nearly 4 kcal mol −1 . These two ruthenium(ii ) terpyridine complexes were investigated for their interactions with DNA employing UV-Vis spectroscopy, DNA viscosity measurements and fluorescence quenching measurements. The high binding constants obtained in the DNA binding studies ( K b = 10 4 –10 5 M −1 ) suggest a strong binding of the complexes to calf thymus (CT) DNA. Competitive studies with ethidium bromide (EB) showed that the complexes can displace DNA-bound EB, suggesting strong competition with EB ( K sv = 1.5–2.5 × 10 4 M −1 ). In fact, the results indicate that these complexes can bind to DNA covalently and non-covalently. In order to gain insight of the behavior of a neutral compound, besides the four previously synthesized cationic complexes [Ru(Cl-tpy)(en)Cl][Cl] (1 ), [Ru(Cl-tpy)(dach)Cl][Cl] (2 ), [Ru(Cl-tpy)(bpy)Cl][Cl] (3 ) and [Ru(tpy)Cl3 ] (P2 ), a new complex, [Ru(Cl-tpy)(pic)Cl] (4 ), was used in the biological studies. Their cytotoxicity was investigated against three different tumor cell lines, i.e., A549 (human lung carcinoma cell line), HCT116 (human colon carcinoma cell line), and CT26 (mouse colon carcinoma cell line), by the MTT assay. Complexes1 and2 showed higher activity than complexes3, 4 andP2 against all the selected cell lines. The results on in vitro anticancer activity confirmed that only compounds that hydrolyze the monodentate ligand at a reasonable rate show moderate activity, provided that the chelate ligand is a hydrogen bond donor.